Effects of Solar Drying on the Structural and Thermodynamic Characteristics of Bee Pollen - Zuluaga Dominguez, Carlos Mario; Castellanos Páez, Brian Alberto; Durán Jiménez, Andrés; Fuenmayor, Carlos Alberto; Quicazán, Marta Cecilia (Vitae, 2022)
Background: Bee pollen is a natural product collected and transformed by bees, intended for human consumption, given its nutritional and bioactive richness. The fundamental operation of adequacy is drying, which allows its preservation, avoiding chemical or microbiological degradation, typically using tray dryers with hot air that use electricity or fuel for heat generation. Solar drying is an alternative that uses radiation as an energy source. However, it should be ensured that this type of process guarantees the quality of the product while not degrading its properties and, therefore, maintaining its morphological integrity. Objective: to establish the effect of solar drying on bee pollen structure compared to the conventional cabin dehydration process. Methods: Bee pollen was dehydrated using two types of dryers: a solar dryer and a forced convection oven. The solar dryer operating conditions were an average temperature of 19-35 °C with a maximum of 38 °C and average relative humidity (RH) of 55 %. Cabin dryer operating conditions were a set point temperature of 55 ± 2 °C and 10 % RH average humidity. The morphologic and thermodynamic properties of dried bee pollen, such as phase transition enthalpy through Differential Scanning Calorimetry (DSC), porosity and surface area through surface area analysis, and microscopic surface appearance by Scanning Electron Microscopy (SEM), were measured. Results: The results showed dry bee pollen, both in the cabin dryer and solar dryer, did not suffer morphological changes seen through SEM compared to fresh bee pollen. Moreover, surface area analysis indicated the absence of porosity in the microscopic or macroscopic structure, demonstrating that solar or cabin drying processes did not affect the specific surface area concerning fresh bee pollen. Additionally, Differential Scanning Calorimetry (DSC) and Thermo Gravimetric Analysis (TGA) showed that endothermic phase transitions for dried bee pollen by cabin or solar dryer were at 145 °C and 160 °C, respectively. This can be mostly associated with free water loss due to the morphological structure preservation of the material compared to fresh bee pollen. Conclusion: These results demonstrate that solar drying is a reliable alternative to bee pollen dehydration as there were no effects that compromised its structural integrity.